Peptide fraction from sturgeon muscle by pepsin hydrolysis exerts anti-inflammatory effects in LPS-stimulated RAW264.7 macrophages via MAPK and NF-κB pathways - Ruichang Gao; Wanghui Shu; Yang Shen; Quancai Sun; Wengang Jin; Dajing Li; Ying Li; Li Yuan (Food Science and Human Wellness)
Previous studies have suggested that polypeptides extracted from milk, soybean, fish, eggs, and meat possess potential anti-inflammatory effects. To date, few studies have reported the anti-inflammatory function of sturgeon peptides and their underlying mechanisms are unknown. The current study was therefore to determine the anti-inflammatory potential of sturgeon peptides with lipopolysaccharide (LPS)-induced RAW264.7 inflammatory model. Pepsin hydrolysate (PeH) was purified by ultrafiltration and Sephadex G-15 gel filtration chromatography. PeH significantly reduced the inflammatory mediator (NO) and inflammatory cytokines (IL-6, TNF-α and IL-1β) expression in a dose-dependent manner. Moreover, the purified sturgeon peptide (F2) possessed strong antioxidant potential and effectively inhibited DPPH and ABTS free radicals. F2 significantly suppressed the expression of MAPK, IκBα, and NF-κB p65, indicating that F2 exerted anti-inflammatory influence by the inhibition of MAPK and NF-κB pathways.